Land Subsidence in the North Coastal Semarang City for Socioeconomic Activities - Giovanie, Yossi; Azzarra, Aisya Bella; Hidayatullah, Ahmad Fauzan; Hariz, Anif Rizqianti (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2023)
The city of Semarang is a coastal area that often experiences the phenomenon of land subsidence which causes sea level rise for decades. From several sub-districts directly adjacent to the Java Sea area, the worst impact of the disaster was experienced by North Semarang District, Bandarharjo Village. The impact of disaster greatly affected the lives of Bandarharjo residents, starting from the aspect of social, economic, and social activities. This makes the residents of Bandarharjo required to be able to survive to adapt to this phenomenon. This study aims to determine how the impact of the land subsidence phenomenon on the social and economic activities of the Bandarharjo Village community. This study uses a qualitative method, namely by analyzing all phenomena that occur in the field. The research data was taken by seeking information through observation, interviews, and document review. The people of the Bandarharjo Village must set aside their salaries to buy land to avoid tidal floods due to land subsidence in the Bandarharjo Village. This will impact the economic conditions of the Bandarharjo Village community, which has low-income jobs.